Analisis Kinerja dan Pengembangan Bisnis Aroma Vegetarian di Kota Palembang - YANFI NATALIA WIJAYA; Clarins Anastasia; Yulizar Kasih (Universitas Multi Data Palembang, 2026)
This study aims to formulate and evaluate the business development of Aroma Vegetarian, a plant-based culinary enterprise in Palembang City. The scope of the study includes product, marketing, service, and business performance aspects. The methods applied consist of field observation, a customer satisfaction survey involving 50 respondents, and descriptive analysis of sales data and marketing strategies. The findings indicate that grilled menu innovation, brand identity enhancement, and digitalization increase customer interest and satisfaction, with Grilled Seafood Fried Rice as the leading product. The study concludes that structured business development efforts can improve competitiveness and support the sustainability of Aroma Vegetarian.